Robin Sequence: 5-Year Speech Outcomes—A Case-Control Study. Issue 3 (2nd October 2021) - Schwaiger, Michael; Cook, Hannah; Jordan, Zoe; Edmondson, Sarah-Jayne; Mischak, Irene; Wallner, Jürgen; Atherton, Duncan; Haers, Piet; Timoney, Norma; Ferguson, Louisa
Abstract : Background: Pierre Robin sequence (Robin sequence) is defined as the triad of micrognathia, glossoptosis, and airway obstruction. It is frequently associated with palatal clefting. In recent years, increased interest in speech outcomes of cleft patients diagnosed with Robin sequence has been shown. Methods: Speech outcomes of cleft patients with Robin sequence were assessed at age 5 in comparison with a cleft palate–only cohort. Speech parameters were evaluated according to the Cleft Audit Protocol for Speech-Augmented and analyzed using the National Audit Standards for Speech (United Kingdom). All patients were treated in the same institution during the same period (2005 to 2012). Subjects who needed nasopharyngeal airway support and those whose airway was managed by positioning only were eligible. Results: Fifty-one cleft patients diagnosed with Robin sequence were included in this study. Outcomes were compared to those of 128 nonsyndromic cleft palate–only patients. Patients with Robin sequence were shown to present with a significantly higher rate of cleft speech characteristics in comparison to the reference cohort ( p = 0.001). Furthermore, it was shown that Robin sequence is associated with a significantly higher rate of secondary speech surgery for velopharyngeal dysfunction before the age of 5 ( p = 0.016). Robin sequence patients with a nasopharyngeal airway presented with a higher rate of cleft speech characteristics compared to Robin sequence patients managed with positioning only. Conclusion: Cleft patients with Robin sequence are more likely to need further surgery to correct velopharyngeal dysfunction before the age of 5 and are more prone to present with cleft speech characteristics at the age of 5. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.